Copeptin in Severe Mitral Regurgitation Caused by Degenerative Mitral Disease - (:unkn) unknown (My University, 2017)
Introduction: Copeptin is known to be increased in cardiac heart failure. The role of copeptin in patients with severe mitral regurgitation has not been assessed in patients with preserved ejection fraction. The objective of this study is to evaluate the role of severe mitral regurgitation caused by degenerative mitral disease in copeptin release.Patients and Methods: 39 patients with degenerative mitral regurgitation (DMR group) and 30 control sub- jects (control group) were included in the study. The clinical and echocardiographic findings were recorded. Blood samples were obtained in 15 min before echocardiographic examination for determination of plasma copeptin. Global left ventricular longitudinal and circumferential strains were evaluated by applying 2D speckle-tracking imaging.Results: There was no statistical difference among copeptin levels of all groups (median values are for DMR:10.7 (9.0-17.1); control group:13.2 (10.6-20.7; p= 0.42). GCSTR and GLSTR were significantly lower in the DMR group (-19.2 ± 5.5 vs. -23.8 ± 5.3; p= 0.002 and -17.1 ± 4.3 vs. -19.9 ± 2.4 p= 0.002 respectively).LAV (83.7 ± 38.8 vs. 34.1 ± 7.5 p= 0.0001), E/e’ (9.6 ± 4.0 vs. 6.0 ± 1.4; p= 0.0001), and E/A (1.79 ± 0.5 vs.0.9 ± 0.24 p= 0.0001) ratios were significantly higher in the DMR group.Conclusion: Our study demonstrated that there is no significant change in serum copeptin concentrations in severe mitral regurgitation due to degenerative mitral disease. This can be attached to the filling changes of left atrium, atrial stretch receptors, and increased stroke volume.

Giriş: Kopeptinin kalp yetersizliğinde yükseldiği bilinmektedir. Korunmuş ejeksiyon fraksiyonlu ileri mitral yetersizliği olan hastalarda kopeptinin rolü bilinmemektedir. Bu çalışmanın amacı kopeptin salınımında deje- neratif mitral hastalığa bağlı ileri mitral yetersizlikliğinin rolünü değerlendirmektir. Hastalar ve Yöntem: Dejeneratif ileri mitral yetersizliği olan 39 hasta (DMR grubu) ve 30 kontrol deneği (kontrol grubu) çalışmaya alındı. Klinik ve ekokardiyografik bulgular kayıt altına alındı. Plasma kopeptin düzeyini belirlemek için ekokardiyografik incelemeden 15 dakika önce kan örnekleri alındı. Global sol ventri- küler longitudinal ve sirkumferensiyal değerlendirme 2D specle tracking görüntüleme ile yapıldı. Bulgular: Gruplar arasında kopeptin düzeyleri açısından anlamlı fark yoktu (median değerleri DMR: 10.7 (9.0-17.1); kontrol grup:13.2 (10.6-20.7) (p= 0.42)). GCSTR ve GLSTR değerleri DMR grubunda control grubuna göre daha düşüktü ( -19.2 ± 5.5 vs. -23.8 ± 5.3; p= 0.002 ve -17.1 ± 4.3 vs. -19.9 ± 2.4 p= 0.002 sırasıyla). LAV (83.7 ± 38.8 vs. 34.1 ± 7.5 p= 0.0001), E/e’ (9.6 ± 4.0 vs. 6.0 ± 1.4; p= 0.0001) ve E/A (1.79 ± 0.5 vs. 0.9 ± 0.24 p= 0.0001) oranları DMR grubunda anlamlı olarak yüksekti. Sonuç: Bizim çalışmamız; dejeneratif mitral hastalığa bağlı ileri mitral yetersizliğinde kontrol grubuna göre kopeptin düzeylerinde anlamlı değişiklik olmadığını göstermiştir. Bu bulgu sol atriyal dolum değişiklikleri, atriyal stretch reseptörleri ve artmış stroke volüm ile ilişkilidir.
Dejeneratif Mitral Hastalığa Bağlı İleri Mitral Yetersizliğinde Kopeptin
Keywords: Anestezi; Kalp ve Kalp Damar Sistemi; Periferik Damar Hastalıkları